2013
DOI: 10.1371/journal.pone.0079906
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Worker Contact Networks and the Prevention of Hospital-Acquired Infections

Abstract: We present a comprehensive approach to using electronic medical records (EMR) for constructing contact networks of healthcare workers in a hospital. This approach is applied at the University of Iowa Hospitals and Clinics (UIHC) – a 3.2 million square foot facility with 700 beds and about 8,000 healthcare workers – by obtaining 19.8 million EMR data points, spread over more than 21 months. We use these data to construct 9,000 different healthcare worker contact networks, which serve as proxies for patterns of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 45 publications
(46 reference statements)
2
34
0
Order By: Relevance
“…28 Understanding how healthcare workers move and interact with patients within hospitals can help inform both disease surveillance approaches and infection-control interventions. [29][30][31][32] Understanding how patients move throughout a state will help inform both disease surveillance approaches and infection-control interventions for a wide range of infections. For example, in our hospital graph, the clustering identified three distinct clusters, yet all the clusters are also linked by hospital transfers.…”
Section: Discussionmentioning
confidence: 99%
“…28 Understanding how healthcare workers move and interact with patients within hospitals can help inform both disease surveillance approaches and infection-control interventions. [29][30][31][32] Understanding how patients move throughout a state will help inform both disease surveillance approaches and infection-control interventions for a wide range of infections. For example, in our hospital graph, the clustering identified three distinct clusters, yet all the clusters are also linked by hospital transfers.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Mastrandrea [26], studying a single infectious disease ward using radio frequency tracking devices, also found that physicians had the highest number of contacts with other health care workers, although this was within a total pool of only 22 HCWs. A study by Curtis et al [16], used movement patterns from electronic medical records to suggest that resident physicians and nurses had the most frequent HCW contacts. While this conflicts with other findings, their definition of a contact differs significantly and did not include contacts in areas where electronic medical records fail to capture.…”
Section: Discussionmentioning
confidence: 99%
“…These studies capture patient movement as it pertains explicitly to the more complex clinical services they receive but fail to capture HCW social or casual movement, such as visits to the cafeteria or meeting rooms, or some types of clinical contact (e.g. a second staff member assisting with patient mobilization or bathing, or cross-covering a colleague on break) [14][15][16]. Contact patterns for HCWs have been examined using radio frequency identification (RFID) tags, mote-based sensors, and direct observation [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…To examine patient mobility, we use graph theory, the mathematical analysis of networks that allows us to construct a network of movement how hospital units are connected by patient movement between them [6]. Network analysis has been previously used to examine intra-hospital transfers and ambulatory care [7,8,9], but limited studies of inter-hospital mobility [10,11]. Grouping patients by their location in a hospital gives us the opportunity to examine susceptibility and risk of CDI from a population perspective, and calculation of network centrality [6] provides us with context of how inpatient units are connected in our hospital via patient transfers.…”
Section: Introductionmentioning
confidence: 99%